Atlas of Miniature Adventures : A Pocket-Sized Collection Of Small-Scale Wonders - Emily Hawkins & Lucy Letherland
Discover the world's smallest adventures with this beautifully illustrated journey around the world from the award-winning team behind Atlas of Adventures. Explore seven continent maps and learn about the best small-scale adventures on Earth - whether you're taking a ride on the world's largest miniature railway, sending a letter with the world's smallest post office or cruising coral reefs with the smallest seahorse, this book brings together coolest miniature adventures from the four corners of the globe.